Terminal velocity of spherical particles falling through non-Newtonian suspensions - Machač, Ivan; Ulbrichová, Iva; Elson, Tim P.; Cheesman, David J. (Univerzita Pardubice, 1996)
The terminal falling velocities of glass, steel, and lead spheres in shear-thinning suspensions of kaolin and titanium dioxide in water solutions of glycerol have been measured. Overall, 130 spherical particle – suspension combinations gave been tested giving a Reynolds number range of 0.001 < Retn < 452. The suitability of the correlations presented for the prediction of the drag coefficient of spheres falling through power-law and Herschel–Bulkley model fluids, has been evaluated by comparing their predictions with the above-mentioned experimental data.